THE RELATIONSHIP OF ACADEMIC PROCRASTINATION AND ACADEMIC DISHONESTY IN UNDERGRADUATE MEDICAL STUDENTS - Dwita Oktaria; Sharlene Sabrina Azzahra; Dian Isti Angraini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The act of academic dishonesty is a dishonest act taken by students in completing assignments and examinations which include several attempts such as cheating and plagiarism. Studies show that 20% of students begin cheating behavior from the first year of college. One of the patterns of behavior related to academic dishonesty is procrastination. Academic procrastination is a form of behavior when someone delays starting a job or completing it.Aims: This study aims to illustrate academic procrastination, academic dishonesty, and the relationship between procrastination habits and academic dishonesty among undergraduate medical students at Faculty of Medicine, Universitas Lampung.Methods: This study is an observational analytic study using a cross-sectional design. The research respondents were 120 undergraduate medical students from Faculty of Medicine Universitas Lampung. The sampling method used proportionate stratified random sampling. Data were collected using the Procrastination Assessment Scale-Students questionnaire and the Academic Practices Survey.Results: The results of this study are processed using computer software and Gamma testing method. Obtained r = 0.464 and p = 0.428 (p>0.05).Conclusion: There is no relationship between the academic procrastination habits and academic dishonesty in undergraduate medical students at Faculty of Medicine, Universitas Lampung.